Nano-sized carriers in gene therapy for renal fibrosis in vivo. (1st January 2017) - Miyazawa, Haruhisa; Hirai, Keiji; Ookawara, Susumu; Ishibashi, Kenichi; Morishita, Yoshiyuki
ABSTRACT: Renal fibrosis is the final common pathway leading to end-stage renal failure regardless of underlying initial nephropathies. No specific therapy has been established for renal fibrosis. Gene therapy is a promising strategy for the treatment of renal fibrosis. Nano-sized carriers including viral vectors and non-viral vectors have been shown to enhance the delivery and treatment effects of gene therapy for renal fibrosis in vivo . This review focuses on the mechanisms of renal fibrosis and the in vivo technologies and methodologies of nano-sized carriers in gene therapy for renal fibrosis. RESPONSIBLE EDITOR Alexander Seifalian Director of Nanotechnology & Regenerative Medicine Ltd., The London BioScience Innovation Centre, London, UNITED KINGDOM